WHAT FACTORS AFFECT STUDENTS’ WHISTLEBLOWING INTENTIONS? - Nuraini, Rafita Yayang; Pujiningsih, Sri (Faculty of Economics and Business University of Mataram, 2021)
Accounting students' courageous behavior in exposing fraud or violation is critical for their future careers as accountants and other professions. This paper attempts to explain the variables that influence whistleblowing intentions through the Theory of Planned Behavior (TPB) lens. This study used a survey to gather data from 154 accounting students. The effect of attitude variables, subjective norms, and behavioral control on accounting students' whistleblowing intentions was examined using a regression test. The regression analysis indicated that all three variables influenced whistleblowing intentions positively. Among the three variables, attitude towards behavior has the biggest impact on whistleblowing intentions, at 37%. This could be interpreted as the need of building accounting students' attitude character to encourage whistleblowing action. Accounting lecturers, as indicators of student subjective norms, play a critical role in developing these characters. This study has theoretically confirmed the applicability of the TPB. The findings of this study assist policymakers in developing a university-based whistleblowing system.